2021
DOI: 10.1021/jacs.1c09280
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Like Hydroxylation of Aliphatic C–H Bonds From an Isolable Co-Oxo Complex

Abstract: The selective hydroxylation of aliphatic C–H bonds remains a challenging but broadly useful transformation. Nature has evolved systems that excel at this reaction, exemplified by cytochrome P450 enzymes, which use an iron-oxo intermediate to activate aliphatic C–H bonds with k 1 > 1400 s–1 at 4 °C. Many synthetic catalysts have been inspired by these enzymes and are similarly proposed to use transition metal-oxo intermediates. However, most examples of well-characterized transition metal-oxo species are not ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…Identification and reactivity studies of high-valent Fe-OH , or Mn-OH , species are reported in the literature. However, to the best of our knowledge, spectroscopic characterization and reactivity studies of the Co-OH complex above +III redox level is not explored, although a few Co III (OH) complex has been characterized spectroscopically. , Characterization of metastable reaction intermediates plays a key role in understanding the reaction mechanism of several bioinspired reactions. A few Co-oxygen reaction intermediates, such as Co III (O 2 • ), Co III (O 2 – ), and Co IV (O) species, have been characterized, and their reactivities were investigated .…”
Section: Resultsmentioning
confidence: 99%
“…Identification and reactivity studies of high-valent Fe-OH , or Mn-OH , species are reported in the literature. However, to the best of our knowledge, spectroscopic characterization and reactivity studies of the Co-OH complex above +III redox level is not explored, although a few Co III (OH) complex has been characterized spectroscopically. , Characterization of metastable reaction intermediates plays a key role in understanding the reaction mechanism of several bioinspired reactions. A few Co-oxygen reaction intermediates, such as Co III (O 2 • ), Co III (O 2 – ), and Co IV (O) species, have been characterized, and their reactivities were investigated .…”
Section: Resultsmentioning
confidence: 99%
“…This lability of the pyrazolyl N–B linkage also reduces the chemical and thermal stability of tris (pyrazolyl)­borates . Compared with emerging scorpionate ligands, classic tris (pyrazolyl)­borates are relatively weak electron donors, a limitation when studying high-valent reactive metals …”
Section: Introductionmentioning
confidence: 99%
“…The discoveries of high-valent metal-oxo species as key intermediates in a variety of enzymatic transformations have inspired numerous biomimetic and bio-inspired efforts trying to understand the structural and spectroscopic properties and substrate oxidation reactivities of these species. , While a large inventory of synthetic M­(IV)O complexes for first-row early and middle transition metal elements (Cr, Mn, and Fe) have become available, high-valent metal-oxo complexes for late transition metals (Co, Ni, and Cu) are rare, as predicted by the classic bonding theory. , Alternatively, diverging the synthetic effort from the metal-oxo territory to develop non-oxo-metal complexes of late transition metals appears to be an effective strategy that provides more flexibility to study the rich chemistry of their high-valent derivatives . For example, a number of groups, including us, have described oxo- and non-oxo-Co­(IV) species capable of oxidizing sp 3 C–H bonds. For Ni and Cu, the +3 oxidation state is typically considered as “high valent”. A number of Ni­(III)- and Cu­(III)-hydroxo, carboxylate, and halide complexes are strong oxidants and hydrogen atom transfer (HAT) reagents; however, examples of these two metals having formal +4 oxidation states are rare.…”
Section: Introductionmentioning
confidence: 99%